Advances in KEAP1-based PROTACs as emerging therapeutic modalities: Structural basis and progress - Jing Chen; Disheng Feng; Rui Zhu; Hua Li; Lixia Chen (Redox Biology)
Kelch-like ECH-associated protein 1 (KEAP1) functions as a substrate adaptor for the Cullin 3-RING E3 ligase complex, mediating the ubiquitination and subsequent proteasomal degradation of nuclear factor erythroid 2-related factor 2 (NRF2). This regulatory mechanism maintains cellular redox homeostasis by preventing NRF2 overactivation. Proteolysis-targeting chimeras (PROTACs) have emerged as a novel therapeutic strategy that harnesses the ubiquitin-proteasome system for targeted protein degradation. Recent advancements have expanded the repertoire of E3 ligases exploitable for PROTAC design, with KEAP1 identified as a promising candidate. This review provides a comprehensive overview of the structural and functional characteristics of KEAP1, detailing its interactions with NRF2 and Cullin 3. The development of KEAP1- recruiting PROTACs utilizing ligands derived from different classes of known KEAP1 inhibitors—including short peptides, covalent small molecules (e.g., CDDO derivatives), and non-covalent inhibitors (e.g., KI696)—is discussed, highlighting the potential to diversify the available E3 ligase recruiters. Recent progress in developing KEAP1-based PROTACs targeting BRD4, CDK9, FAK, Tau and KEAP1 itself is highlighted, with particular emphasis on ligand optimization strategies employed to enhance degradation efficacy and specificity. Elucidating the structural basis of KEAP1 interactions provides crucial insights for advancing PROTAC applications. However, current challenges in KEAP1-based targeted protein degradation warrant further investigation to fully realize its therapeutic potential. Future research should focus on optimizing KEAP1 ligand properties and exploring novel protein targets amenable to degradation via KEAP1 recruitment to further advance this innovative therapeutic modality.